Study protocol of a phase II clinical trial evaluating the efficacy of neoadjuvant intraperitoneal and systemic albumin-bound paclitaxel combined with camrelizumab and S-1 in the treatment of patients with exfoliative cell-positive gastric cancer - Lv, Jingxia; Wu, Jiaxiang; Wu, Haotian; Ding, Ping’an; Guo, Honghai; Yang, Peigang; Tian, Yuan; Liu, Yang; Zhao, Qun (Frontiers in Oncology, 2023)
Background: Currently, gastric cancer with positive lavage cytology without gross peritoneal dissemination (GC-CY1) is a special type of metastatic form with poor prognosis. Consensus guidelines on treatment strategies for patients with GC-CY1 have not been established. This study involves a single-arm, prospective, phase II clinical trial to examine the efficacy and safety of neoadjuvant intraperitoneal and systemic (NIPS) albumin-bound paclitaxel combined with Camrelizumab and S-1 in the treatment of GC-CY1 patients.Methods/design: This is a prospective single-center exploratory study, and the primary endpoints of the trial are R0 resection rate and conversion rate of abdominal free cancer cells (FCCs), with secondary endpoints of 3-year progression-free survival (PFS); 3-year overall survival (OS); objective remission rate (ORR); disease control rate (DCR); safety and TRG classification.Discussion: This study is the first to apply NIPS albumin-bound paclitaxel combined with Camrelizumab and S-1 to the conversion therapy of GC-CY1 patients. It is speculated that this combination of regimens will increase the negative conversion rate of FCCs by 20%, which will provide innovative insights into conversion treatment ideas for GC-CY1 patients to be managed in a more comprehensive and optimized manner.Trial registration: This trial was registered retrospectively in the ClinicalTrials.gov on 30th of June 2022: NCT05410847.